Bladder injuries during obstetrical and gynecological surgeries - Vaidya, Beena; Chaudhari, Manish; Parmar, Deep; Chaudhari, Vipul; Daginawala, Taha; Shah, Ritesh (International Surgery Journal, 2017)
Background: The reproductive and urinary tracts in women are closely related anatomically and embryologically. Knowledge of this anatomy plays an important role in the prevention of urinary tract injury during gynaecologic surgery. The primary approach to prevention is careful surgical dissection and knowledge of the position of urinary tract structures within the surgical field. Methods: Prospective interventional study consisted of 28 patients with obstetrics and gynecological surgeries was carried out at department of surgery, new civil hospital, Surat during December 15th to January 16th. Out of 28 patients 13 patients had bladder injuries which repaired and studied in detail. Results: Out of these 28 patients undergone various obstetrics and gynecological surgeries, 13 patients were having iatrogenic urinary bladder injuries. Bladder injury occurred commonly during in LSCS and in hysterectomies. Out of 13 urinary bladder injuries, 8 injuries repaired in 2 layers by Vicryl 2-0 without insertion of SPC and 5 injuries were managed by primary repair with vicryl 2-0 with insertion of SPC (SPC= suprapubic cystostomy). Conclusions: Surgery adjacent to or within urinary bladder continue to result in occasional iatrogenic injury. These injuries can be minor with no long-term sequelae, or they can result in significant morbidity and inconvenience to patients.